A Dual Role for Death Receptor 5 in Regulating Cardiac Fibroblast Function - Tanner, Miles A.; Grisanti, Laurel A. (Frontiers in Cardiovascular Medicine, 2021)
The fibrotic response is involved in nearly all forms of heart failure and dysregulated responses can lead to enhanced cardiac dysfunction. TNF-related apoptosis-inducing ligand (TRAIL) and its receptor, death receptor (DR) 5, are associated with multiple forms of heart failure, but their role in the heart is poorly defined. Our previous study identified DR5 expression on cardiac fibroblasts however, the impact of DR5 on fibroblast function remains unexplored. To investigate the role of DR5 in cardiac fibroblasts, a variety of fibroblast functions were examined following treatment with the endogenous ligand, TRAIL, or small molecule agonist, bioymifi. DR5 activation did not induce apoptosis in naïve fibroblasts but activated ERK1/2 signaling to increase proliferation. However, upon activation and differentiation to myofibroblasts, DR5 expression was elevated and DR5 agonists induced caspase 3 activation resulting in myofibroblast apoptosis. To investigate the impact of DR5 regulation of fibroblasts in vivo, a chronic isoproterenol administration model of heart failure was used. Wild-type (WT) mice receiving isoproterenol had increased hypertrophy, cardiomyocyte death and fibrosis and decreased contractility compared to vehicle treated animals. DR5 knockout (KO) mice had no overt baseline phenotype however, following isoproterenol infusion, increased cardiomyocyte death and hypertrophy in comparison to isoproterenol treated WT animals was observed. DR5KO mice had an augmented fibrotic response with isoproterenol treatment compared with WT, which corresponded with additional decreases in contractility. These findings identify a dual role for DR5 in cardiac fibroblast function through enhanced naïve fibroblast proliferation, which switches to a pro-apoptotic function upon differentiation to myofibroblasts. This is important in heart failure where DR5 activation suppresses maladaptive remodeling and may represent a novel therapeutic target for the treatment of heart failure.